TOTAL FLAVONOID AND ANTIOXIDANT ACTIVITY OF ETHANOL EXTRACT FROM JAVA PLUM (Syzygium cumini L.) LEAF - Muthmainah Tuldjanah; Ayu Wulandari (GEMA KESEHATAN, 2022)
Juwet leaf is a plant with antioxidant properties that protect against free radicals. The simplicia ethanol extract of juwet leaves used came from the city of Palu, Central Sulawesi. Extraction of chemical content from juwet leaves (Syzygium cumini L.) was carried out by maceration method. In this study, to determine the levels of flavonoid compounds and antioxidant power in the sample extract, a compound analysis was carried out using a UV_Vis spectrophotometer. Total flavonoid content was determined from the absorbance value obtained from a wavelength of 510 nm by using Visible spectrophotometry. Antioxidant activity was obtained by measuring the reducing activity of the ethanol extract of juwet leaves on the free radical DPPH (1,1-Diphenyl-1-picrylhydrazil) by Visible spectrophotometry with a wavelength of 517 nm. An antioxidant activity test was carried out using quercetin as a comparison. The results showed that the ethanol extract of juwet leaves had low total flavonoid content with weak antioxidant activity compared to quercetin. Keywords: Antioxidants, Flavonoids, Juwet leaves